Expression of Mucins in Salivary Gland Mucoepidermoid Carcinoma - Robinson, Liam (Head Neck Pathol, 2020)
Mucoepidermoid carcinoma (MEC) is the most common malignant salivary gland tumour in both adults and children. Histological grading of MEC is subjective, but plays an important role in predicting patient prognosis. Epithelial mucin (MUC) status may aid in establishing a more accurate grade. This study aimed to investigate the expression of various mucins (MUC1, MUC2, MUC4 and MUC5AC) in MECs to determine a possible correlation with tumour grade. Fifteen cases of each tumour grade (low-, intermediate-, and high-grade) were retrieved from the pathology archives of the Department of Oral Pathology and Oral Biology at the University of Pretoria. The patients included 23 men and 22 women, and ranged from 13 to 85 years (mean 49.8 years). Sections from formalin-fixed paraffin-embedded (FFPE) tissue were used for fluorescence in situ hybridization (FISH) for MAML2 rearrangements and MUC immunohistochemical analysis. The percentage immunohistochemical expression of the neoplastic mucous cells was evaluated first, followed by the overall percentage expression of all tumour cells. The results indicated that MUC1 overexpression may be a reliable marker of high-grade MECs, whereas MUC4 overexpression may be more indicative of low-grade tumours. MUC5AC expression was considered an unreliable marker in determining grade. MUC2 was only expressed in a single case of MEC and may be considered a useful marker to exclude MEC as a diagnostic possibility. This study demonstrates that MECs show an altered MUC expression pattern that can be used for diagnostic purposes and to aid in establishing a more accurate tumour grade.